Is a pandemic as good as a rest? Comparing athlete burnout and stress before and after the suspension of organised team sport due to Covid-19 restrictions, and investigating the impact of athletes' responses to this period. (May 2022) - Woods, Siobhán; Dunne, Simon; Gallagher, Pamela; Harney, Sibéal
Abstract: The COVID-19 pandemic resulted in social-distancing measures and the suspension of organised sport globally, and has been shown to have negatively impacted mental health. However, athletes may have experienced reprieve from sport demands, which have previously been linked with maladaptive responses such as burnout and stress. The aims of this study were (1) compare levels of burnout and stress reported by Gaelic games athletes pre- and post-COVID-19 suspension period, (2) explore how athletes utilised and perceived this period and the return to sport, and (3) examine the implications of this for burnout. Participants completed an online questionnaire, which included the athlete burnout questionnaire, perceived stress scale, sport emotion questionnaire, demographic questions, weekly training hours, and other hours for sport (e.g. travel) before Covid-19 (BC-19) and after the Covid-19-induced suspension (AC-19_S). Questions relating to how athletes utilised (e.g. training focus) and perceived (positive/negative impact) the period were included AC-19 S. Data was compared across time-points and we explored predictors of burnout AC-19_S. Ninety-two athletes completed the questionnaire at both time-points. No significant differences in burnout or stress were identified, suggesting the suspension period did not significantly impact these variables. Burnout BC-19, stress AC-19_S, unpleasant emotions about returning to sport and using the period to rest/recover positively predicted burnout AC-19_S. Reduction in other hours across time-points and pleasant emotions about returning predicted lower burnout. Results suggest an athletes' response to a suspension period and subsequent return to sport can impact feelings of burnout, and may have implications for future unanticipated change events. Highlights: No significant differences in burnout or stress pre- and post-suspension of sport. Athletes experienced positive and negative impacts of the suspension of sport. Less off-field hours and pleasant emotions about resuming sport predict lower burnout. A focus on rest and unpleasant emotions about resuming sport predict higher burnout.